Faktor-Faktor Yang Mempengaruhi Sikap Pasangan Usia Subur (PUS) Melakukan Skrining Kanker Serviks Metode Iva Di Wilayah Kerja Puskesmas Kota Wilayah Utara Kota Kediri - Ira Titisari; Triatmi Andri Yanuarini; Sumy Dwi Antono (Akademi Keperawatan Dharma Husada Kediri, 2017)
The number of cases of cervical cancer in Kediri continues to increase, in 2004: 165 cases, 2005: 170 cases and 2006: 175 cases. Cumulative target achievement in 2009-2013 amounted to 12.16%. Coverage is still far below the annual target of Kediri has stepped fifth year that is equal to 80%.The purpose of this study was to analyze the factors that influence women's attitudes Couples of Childbearing Age for cervical cancer screening methods IVA in Puskesmas City area north of Kediri. Design research is analytic observational cross-sectional approach. The population is all Couples of Childbearing Age women aged 30-50 years in the region of Northern Regional Health Center in the amount of 400 samples of 50 people were taken by cluster random sampling. The analysis used bivariate correlation analysis Chi-square and multivariate analysis using multiple logistic regression.The result of this research is there is a relationship between knowledge (p-value = 0.00), resources (p-value = 0.001), family support (p-value = 0.001) and personal experiences (p-value = 0.016) with the attitude of women Couples of Childbearing Age did IVA cervical cancer screening method in Puskesmas City area north of Kediri and the factors that influence attitudes Couples of Childbearing Age woman doing IVA cervical cancer screening method in Puskesmas City area north of the town of Kediri is knowledge (p value = 0.003) with a big influence 2,176 .It can be concluded that the factors that influence women's attitudes Couples of Childbearing Age for cervical cancer screening methods IVA in Puskesmas City area north of Kediri is knowledge. Keywords: WomenCouples of Childbearing Age, Attitude, IVA